DETERMINATION OF SIMULTANEOUS IRBESARTAN AND HYDROCHLOROTHIAZIDE BY ULTRAVIOLET SPECTROPHOTOMETRY WITH DUAL WAVELENGTH METHOD - Syahputra, Hafid; Muchlisyam, M. Si. Apt; Masfria, M.S. Apt (Asian Journal of Pharmaceutical Research and Development, 2019)
Objective: The present study was aimed to develop a spectrophotometric method by dual wavelength method in simultaneous analysis of irbesartan and hydrochlorothiazide on tablet preparations without separation. Irbesartan and hydrochlorothiazide are a group of anti-hypertensive drugs that are very effective and safe to use to reduce blood pressure and edema. These drugs often given in combination with these active ingredients can cause problems in quantitative analysis for the quality control of preparations. Methods: The study was carried out experimentally with a spectrophotometric method, one of which was dual wavelength method and then tested its validity based on validation parameters, namely linearity, accuracy, precision, LOD and LOQ and intraday and interday. Then, this method of irbesartan and hydrochlorothiazide in tablet preparations. Results: The results of the study were showed that the application of dual wavelength method on the concentration was carried out at λ 263.4 nm and 281 nm for irbesartan and at λ 243.4 nm and 247.6 nm for hydrochlorothiazide. The results obtained by irbesartan and hydrochlorothiazide on tablets were (108.04 ± 2.696) and (94.28 ± 4.48)% respectively, and with good precision and accuracy. Conclusions: The ultraviolet spectrophotometry method is dual wavelength method successfully applied for the determination of the concentration of irbesartan and hydrochlorothiazide in tablets.